European yearbook of constitutional law 2022: A constitutional identity for the EU? - DE POORTER, Jurgen (Institutional Knowledge at Singapore Management University, 2023)
The European Yearbook of Constitutional Law (EYCL) is an annual publication devoted to the study of constitutional law. It aims to provide a forum for in-depth analysis and discussion of new developments in the field, both in Europe and beyond. This fourth volume of the EYCL addresses the underexplored and contentious topic of whether the EU possesses a constitutional identity of its own.